High selectivity of TiC-CDC for CO2/N2 separation - Silvestre-Albero, Ana; Rico-Frances, Soledad; Rodriguez-Reinoso, Francisco; Kern, Andreas; Klumpp, Michael; Etzold, Bastian; Silvestre-Albero, Joaquin (Carbon, 2013)
A series of carbide-derived carbons (CDC) have been prepared starting from TiC and using different chlorine treatment temperatures (500–1200 °C). Contrary to N2 adsorption measurements at -196 °C, CO2 adsorption measurements at room temperature and high pressure (up to 1 MPa) together with immersion calorimetry measurements into dichloromethane suggest that the synthesized CDC exhibit a similar porous structure, in terms of narrow pore volume, independently of the temperature of the reactive extraction treatment used (samples synthesized below 1000 °C). Apparently, these carbide-derived carbons exhibit narrow constrictions were CO2 adsorption under standard conditions (0 °C and atmospheric pressure) is kinetically restricted. The same accounts for a slightly larger molecule as N2 at a lower adsorption temperature (-196 °C), i.e. textural parameters obtained from N2 adsorption measurements on CDC must be underestimated. Furthermore, here we show experimentally that nitrogen exhibits an unusual behavior, poor affinity, on these carbide-derived carbons. CH4 with a slightly larger diameter (0.39 nm) is able to partially access the inner porous structure whereas N2, with a slightly smaller diameter (0.36 nm), does not. Consequently, these CDC can be envisaged as excellent sorbent for selective CO2 capture in flue-gas streams.
EAM Import::2019-03-13